Cretian Records Held in Public and Private Archives in Turkey - (:unkn) unknown (My University, 2017)
Türkiye'de hem kamu arşivlerinde hem de özel arşivlerde Girit Adası'na dair belgeler bulunmaktadır. Ancak gerek kamu gerekse özel arşivlerin koleksiyonlarının yeterince tanıtılmıyor olması, arşivlerin taşınması ve sayısallaştırma faaliyetlerinin başlaması ile koleksiyonun bir süre bile olsa araştırmaya kapalı olması gibi sebeplerle araştırmacılar bu belgelerin varlığından haberdar olamamaktadır. Araştırmacılar, Girit'e dair belgelere ulaşmak istediklerinde çoğunlukla Başbakanlık Devlet Arşivlerini tercih etmektedirler. Arşivinde Girit'e dair belgeler barındıran bir diğer kamu arşivi de yakın zamanda araştırmaya açılması planlanan Dışişleri Bakanlığı arşividir. Vakıflar Genel Müdürlüğünün arşivinde de Girit'e dair defterler ve belgeler bulunmaktadır. Türkiye'de hak ettiği öneme yeni yeni kavuşan özel arşivlerde de Girit hakkında belgeler vardır. Bu anlamda elinde en fazla belge bulunduran kurum SALT Araştırma'dır ki bu arşiv yukarıda adı geçen kamu arşivlerinin kelimenin tam anlamıyla mütemmim cüzü durumundadır. İslam Araştırmaları Merkezinin (İSAM) de arşiv koleksiyonunda Girit hakkında belgeler bulunmaktadır. Bu çalışmanın amacı, Türkiye'deki kamu arşivlerinde ve özel arşivlerde bulunan Girit belgelerinin niteliği ve niceliği hakkında bilgi vermek, Girit'e ait belgelerin daha kolay ve hızlı bulunması için Girit araştırmacılarına yardımcı olmaktır.

Records relating to the island of Crete are found in both public and private archives in Turkey. However, researchers are unaware of the existence of such records due to reasons such as collections not being sufficiently publicised, archives being moved or collections becoming temporarily unavailable due to digitalization activities. Researchers mainly prefer the Prime Ministerial State Archives when seeking access to Cretan records. Another public archive that houses records relating to Crete is the Foreign Ministry Archives which will be opened its doors to researchers in the near future. Registers and records about Crete can also be found in the archive of the Directorate General of Foundations. Private archives which have only recently achieved the recognition they deserve also hold records relating to Crete. In this sense, the organization that holds the most records relating to Crete is the SALT Research archives which, in the true sense of the term, comprises of an integral part of the collections held by the above named public archives. Records relating to Crete can also be found in the Archival Collection of ISAM (Centre for Islamic Studies). The aim of this study is to provide information on the attributes and quantity of Cretan records held in public and private archives in Turkey, which will in turn, help researchers on Crete to locate records more easily and expeditiously.
Cretian Records Held in Public and Private Archives in Turkey
Keywords: Tarih